HUBUNGAN KETERAMPILAN MEMBACA KRITIS DENGAN KETERAMPILAN MENULIS ARGUMENTASI SISWA KELAS XI SMA NEGERI 12 PADANG - Najmi Hayati (STKIP Pesisir Selatan, 2017)
This research was conducted to describe the relationship of critical reading skill with writing skill of argumentation of class XI students of SMA Negeri 12 Padang. The population of this study is the students of grade XI SMA Negeri 12 Padang. Sampling in this study as many as 30 students by using proportional random sampling technique. This research instrument is an objective test to measure students' critical reading skills, and writing tests to measure argumentation writing skills. Analysis and discussion of data is done by descriptive correlational to know the relationship of critical reading skill with writing skill of argumentation of student of class XI SMA Negeri 12 Padang. Based on the research result, it is concluded that the following three points. First, the level of critical reading skills of grade XI students of SMA Negeri 12 Padang is sufficient (63,16). Second, the level of skill in writing argumentation of class XI students of SMA Negeri 12 Padang is classified as more qualified (72,5). Third, there is a significant positive correlation between critical reading skill and writing skill of class XI student of SMA Negeri 12 Padang.